Research Progress of Chemical Compounds, Pharmacological Effects and Functional Food of Oenanthe javanica - Kaixiang OU; Ronghui GU (Shipin gongye ke-ji, 2022)
Nowadays, more and more people pursuing the life with health, nature and nutrition in diet. Oenanthe javanica, as a kind of vegetable and medicine, contains a lot of nutritional ingredients including protein, vitamins, and minerals. The acrial part of this plant was edible as traditional vegetables. Moreover, O. javanica has been reported to reduce blood press, hypoglycemic and other medicinal values, attributing to its rich content of flavonoids, phenolic acids, and volatile oil. Currently, some related functional food from this plant have been developed as well. To sum up, O. javanica is a prospect resouce to food fields. Herein, the research on chemical components, pharmacological activity and functional food application of this species have been reviewed and summarized through searching the related literatures in recent years from CNKI and Web of Science. Furtherly, the shortcomings and future efforts of O. javanica utilization as food have also put forward. This paper expect to deepen the knowledge of edible and health effects, promote the further research and application, and boost the development of this plant resoure in the food industry.